2016
DOI: 10.1589/jpts.28.1012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Schroth and Pilates exercises on the Cobb angle and weight distribution of patients with scoliosis

Abstract: [Purpose] The purpose of this study was to compare the effect of Schroth and Pilates exercises on the Cobb angle and body weight distribution of patients with idiopathic scoliosis. [Subjects] Twenty-four scoliosis patients with a Cobb angle of ≥20° were divided into the Schroth exercise group (SEG, n = 12) and the Pilates exercise group (PEG, n = 12). [Methods] The SEG and PEG performed Schroth and Pilates exercises, respectively, three times a week for 12 weeks. The Cobb angle was measured in the standing pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(98 citation statements)
references
References 14 publications
0
90
0
8
Order By: Relevance
“…At the beginning each spontaneously growing scoliosis is a gradual low curvature -scoliotic posture (Myers, 2016). After time it reveals the actual development trends (Byun & Han, 2016;Kim & Hwang, 2016). In a pathobiomechanical term, scoliosis is compensated when the original deflection (a) goes smoothly into compensatory, proximal and distal deflection (Porte et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…At the beginning each spontaneously growing scoliosis is a gradual low curvature -scoliotic posture (Myers, 2016). After time it reveals the actual development trends (Byun & Han, 2016;Kim & Hwang, 2016). In a pathobiomechanical term, scoliosis is compensated when the original deflection (a) goes smoothly into compensatory, proximal and distal deflection (Porte et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34][35] AIS symptoms are frequently associated with tumors, inflammation or visceral dysfunction; this would exclude solely conservative management. The studies encompassed by this review did not include that type of patients and, after the intervention, they showed a reduction in symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…All included studies had corrective, therapeutic exercise as the independent outcome measure; 4 referred to it as Schroth exercises, [27][28][29][30] and the other 5 used different terms that covered therapeutic exercise based on self-correction and spinal stabilization. [31][32][33][34][35] The intervention period varied greatly: 3 studies included an intervention that lasted 8-12 weeks, 30,32,35 while 4 conducted interventions for 6 months, 27-29-33 and 2, for 1 year.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations